Response of a forest raptor community to broadcasts of heterospecific and conspecific calls during the breeding season - Bosakowski, T.; Smith, D.G. (Canadian Field-Naturalist, 1998)
We investigated the response of the forest raptor community to broadcasts of all potentially occurring raptors in a New Jersey watershed. Raptors were systematically surveyed using high-volume broadcasts of conspecific and heterospecific calls during the breeding season at a total of 81 survey stations. Results showed 107 responses from 10 species of breeding raptors following 891 broadcasts of 11 species. Among responses that occurred during or after broadcasts, at least 50% of the forest raptor species responded to heterospecific calls. Response rates to conspecific or heterospecific broadcasts were significantly different between hawks (68% heterospecific) and owls (26% heterospecific), suggesting that hawks showed greater heterospecific conflict than members of the owl guild. The hawk guild had a higher species packing (six versus four species) which is thought to increase the likelihood of competition in the community. In addition, most hawks probably need to re-establish territories each spring because the vast majority of them will migrate south for the winter. In contrast, most of the owl guild members are permanent residents and territories may be more permanent. Overall, the prevalence of heterospecific response is an indicator that current competition exists and continues to shape present-day community structure among forest raptors.
Keywords: Behavior; Community; Forest; Hawks; Owls; Raptors; Survey; United States; Vocalizations; breeding season; calling behavior; community structure; dept.bio; forest; intersexual interaction; raptor; ⛔ No DOI found

Toward a professional position on the translocation of problem wildlife - Craven, S.; Barnes, T.; Kania, G. (Wildlife Society Bulletin, 1998)
Keywords: Live capture; Policy; Translocation; Wildlife damage management; dept.bio; ⛔ No DOI found